Lattice dynamics of noble metals on effective three-body interaction - Coelho, A. A.; Shukla, M. M. [UNESP] (My University, 1996)
Quite recently we modified the original model of Sarkar et al. for cubic metals in extending the ion-ion interaction, ion-electron interaction and the introduction of crystal equilibrium condition. We applied our scheme to alkali metals. We studied here the lattice dynamics of noble metals on our approach by calculating phonon dispersion relations along the three principal symmetry directions, [ξ00], [ξξ00] and [ξξξ] and the (θ-T) curves of three noble metals: copper, silver and gold. We obtained reasonable agreement with the experimental findings.